1981
DOI: 10.1128/jvi.37.1.496-499.1981
|View full text |Cite
|
Sign up to set email alerts
|

Frog virus 3 requires RNA polymerase II for its replication

Abstract: The involvement of host cell RNA polymerase II in the replication of frog virus 3 (FV 3) was examined in alpha-amanitin-sensitive or -resistant Chinese hamster ovary (CHO) cells in the presence and absence of alpha-amanitin. In the presence of alpha-amanitin, FV 3 replicated normally in resistant CHO cells but failed to do so in sensitive CHO cells. Synthesis of virus-specific RNAs and proteins was inhibited in sensitive cells infected in the presence of alpha-amanitin, but in alpha-amanitin-resistant cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 16 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…The two-stage sequence of FV3 DNA replication and processing of concatemers can be integrated with previous findings (6,8,9) to provide a scheme of replication that contrasts sharply with the replication strategies of most animal viruses (Fig. 8).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The two-stage sequence of FV3 DNA replication and processing of concatemers can be integrated with previous findings (6,8,9) to provide a scheme of replication that contrasts sharply with the replication strategies of most animal viruses (Fig. 8).…”
Section: Resultsmentioning
confidence: 74%
“…Originally believed to replicate only in the cytoplasm (12), FV3 has since been shown to require a functional nucleus for its replication (9). Recent work has shown that the FV3 genome enters the nucleus, where it is transcribed during early stages of replication (8) probably by a modified host RNA polymerase II (6). Although the viral DNA replicates in both the nucleus and the cytoplasm (8), virus assembly and morphogenesis take place only in the cytoplasm (7,12).…”
mentioning
confidence: 99%
“…Unlike herpesviruses, iridovirid genomes are not infectious, indicating that virion-associated proteins are required to initiate viral gene transcription [32]. Accordingly, immediate-early (IE) and delayed early (DE) viral transcripts are synthesized in reactions mediated by putative virion-associated (for IE transcripts) and virus-encoded (for DE mRNA) transcriptional trans-activators and, at least for IE transcription, host RNA polymerase II [33][34][35]. Among the products of early transcription is a viral DNA polymerase which catalyzes the synthesis of unit-sized copies of the viral genome within the nucleus [36].…”
Section: Early Events/nuclear Phasementioning
confidence: 99%
“…A few FV3 promoters methylated in all 5'-CG-3' dinucleotides have been directly shown to be transcriptionally active [40][41][42] Host RNA polymerase II is thought to be utilized for FV3 mRNA synthesis. 43 Since this polymerase and many of the known cellular transcription factors can be inhibited by promoter methylation, the major question arises of what factors might be involved in keeping the fully 5'-CG-3' methylated FV3 promoters transcriptionally active.…”
Section: Synopsis Of Studies On Dna Methylationmentioning
confidence: 99%